2017
DOI: 10.1159/000457954
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases in Patients with Neuroendocrine Neoplasm: Frequency and Clinical, Therapeutic, and Prognostic Relevance

Abstract: Background: The incidence and prevalence of neuroendocrine neoplasms (NEN) are rising. In view of continuously improving imaging techniques, more than half of the patients present with distant metastases at initial diagnosis. An advanced disease stage negatively correlates with the 5-year survival rate. In stage IV disease, bone metastases (BM) are frequent, yet knowledge concerning their clinical or prognostic relevance is rare. This study presents a single-center experience on the frequency and management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 23 publications
13
91
3
4
Order By: Relevance
“…The current findings suggest that the rate of BMs in patients with NENs is 7%, which appears to be lower than previously reported [6][7][8]. An explanation could be an underdiagnosis of BMs, considering most patients were followed-up using cross-sectional CT imaging, which has limited sensitivity in detecting BMs [17].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The current findings suggest that the rate of BMs in patients with NENs is 7%, which appears to be lower than previously reported [6][7][8]. An explanation could be an underdiagnosis of BMs, considering most patients were followed-up using cross-sectional CT imaging, which has limited sensitivity in detecting BMs [17].…”
Section: Discussioncontrasting
confidence: 73%
“…It is well established that NENs, in particular moderate to high-grade NENs, have the ability to spread to distant sites, including bone [4,5]. Nevertheless, bone metastases (BMs) in NENs are expected to be uncommon events, with several retrospective series reporting an incidence from 12% to as high as 25% in certain subtypes of NENs [5][6][7][8]. Some studies have reported that more than half of patients with NENs with BMs were symptomatic, and that skeletal-related events (SREs) occurred in around 21% [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other survival analyses of midgut NETs, bone metastases have not been assessed separately as a prognostic factor, although in some studies they have probably been included in a miscellaneous category of "distant metastases" along with other sites of extrahepatic disease [6]. A recent paper by Scharf et al [26] including 677 patients with NETs from the EN-ETS centre in Marburg, Germany, showed that bone metastases were present in 12.6% of cases (mainly small intestinal and pancreatic primaries) and were associated with a significantly shorter OS compared to other distant metastases (49 vs. 101 months, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of carcinoid heart disease, mesenteric lymph node metastases, distant abdominal lymph node metastases, liver metastatic burden, extra-abdominal metastases, skeletal involvement and peritoneal carcinomatosis (PC) are independent prognostic factors for OS in SBNEN [157]. Bone metastases have a distinct prognostic impact to that of other distant metastases (inferior OS with the former) [158], and although occurring only in approximately 5% of metastatic GEP NEN, lung metastases have significant detriment to OS which is in addition to that presented by distant metastases at other sites [159]. Multivariate prognostic scores have been developed for both SBNEN and PanNEN in terms of OS or recurrence post-surgery [160][161][162][163].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%